A Study to Identify and Profile Consumer Segments in the Mobile Telecommunication Services Market - Abdin, Md. Shahnawaz (Indian Journal of Marketing, 2020)
Modern day mobile telecommunication network service business is quite challenging and complex. The consumer has been provided with a plethora of options and offers. Unlimited talk time plans, data packages, voice and SMS plans, etc. have changed the way the telecom business operates. Mobile number portability (MNP) has been the biggest game changer. An understanding of consumers at length is thus imperative. This research paper focused on proper segmentation and profiling of consumer segments with an aim to provide sharper and focused marketing programs. The paper highlighted the emergence of two different types of consumer segments namely, the Conventionalist and the Techi. It would be immensely useful for telecom companies to understand consumers’ tastes, habits, preferences, and personality with a view to link them with consumer purchase patterns. Both the segments were found to exhibit quite a few contrasting features and as such could be exploited for concentrated marketing communications. The results indicated that unless and until consumers are regarded as lifetime prospects, companies would find it very difficult to retain consumers. From chota recharge to unlimited talk time, companies have leaped milestones and come a long way, and this has been only possible because of effective segmentation of consumers on geographic, demographic, psychographic, and behavioural bases/parameters. This study used elements of factor analysis and cluster analysis along with behavioural modelling to derive segments’ personality traits.